Exploring the nutritional value, health benefits and concerns associates in selected fermented fish product in Southeast Asia: A review - Binti Atun, Mazlinah; Binti Julmohammad, Norliza; Huda, Nurul; Bin Roslan, Jumardi; Mohd Shariff, Amir Husni; Nisa, Fithri Choirun; Yusra (jurnal1, 2024)
Fermented fish is a staple food in Southeast Asian cuisine with a unique flavor and nutritional properties. This paper provides a comprehensive review of fermented fish, its types and methods of fermentation, nutritional value, health benefits, and risks. The paper highlights traditional and modern methods of fermentation using various types of fish and provides examples of popular fermented fish dishes. The nutritional value of fermented fish is emphasized, including their high protein and amino acid content, omega-3 fatty acids, vitamins, and minerals. Moreover, fermented fish has demonstrated promising health benefits such as improved cardiovascular health, gut health, and anti-cancer properties. However, high sodium content and potential risks of histamine poisoning, or other foodborne illnesses require caution in the consumption of these foods. The paper concludes by underscoring the cultural and public health significance of fermented fish and highlighting the potential for further research on the health benefits and risks of this traditional food.